The inner Blood-Retina Barrier in Age-related Macular Degeneration - Reddy, Avril (Trinity College Dublin. School of Genetics & Microbiology. Discipline of Genetics, 2025)
Age-related macular degeneration (AMD) is the leading cause of blindness in aged populations worldwide. AMD involves the gradual deterioration of central retinal vision overtime but the exact pathobiological mechanisms are poorly understood. In the advanced stages of disease, two forms diverge, the "dry" and "wet" form, each culminating in catastrophic vision loss. In choroidal neovascularisation (CNV), the end-stage of "wet" AMD, rapid vision loss is attributed to the invasion of new "leaky" blood vessels into the retina from the choroid. In the "dry" form, degeneration is slower, triggered by the gradual atrophy of the retinal pigment epithelium (RPE) in the macular region, termed geographic atrophy (GA). As the site of observable deterioration, changes to the RPE and underlying choroid have been the focus of the majority of AMD research. In this project, clinical imaging, animal models and in vitro techniques were utilised to examine how cells of the inner retina influence the development of retinal degeneration. Firstly, destabilising the inner blood retina barrier (iBRB) found at the vasculature of the inner retina in animals fed high dietary cholesterol was found to be an inflammatory trigger that could lead to RPE atrophy that was reminiscent of GA. Secondly, dysregulated expression of CSF1R, a tyrosine kinase receptor crucial for mononuclear phagocyte (MNP) survival and proliferation, was found to increase iBRB permeability and drive the formation of the reticular pseudo drusen (RPD) deposits in mice and in individuals with pathological genetic variants. Finally, as a complex, multifactorial disease, effective or long-lasting treatments are lacking. For this reason, this study aimed to develop a combination therapeutic strategy to target multiple pathological processes. RPE cells derived from induced pluripotent stem cells were enhanced to express a VEGF neutralising drug, aflibercept, and a soluble inhibitor of the complement system, CD59. After subretinal delivery in the spontaneous model of exudative AMD, this approach led to the significant resolution of neovascular lesions. Together, these results demonstrate a role for inner retinal dysfunction, such as iBRB instability and MNP dysregulation, in the pathology of AMD. Further, as a multifactorial disease, uncovering pathological mechanisms in this way will improve our ability to combine therapeutic approaches that will hopefully provide longer-lasting vision saving effects.
APPROVED
Keywords: AMD; iBRB; Claudin-5; Inner retinal vasculature; Inner Blood-Retina Barrier; Age-related Macular Degeneration; CSF1R; Microglia; ALSP; Colony Stimulating Factor 1 Receptor; Adult onset Leukoencephalopathy with axonal Spheroids and Pigmented glia; High Cholesterol Diet; Geographic atrophy; Chorodial neovasculatisation; Reticular pseudodrusen